(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
In this article, the specifics of foreign relations in Arab countries are analyzed based on historical, political, and economic factors. It highlights the post- colonial legacy, the idea of pan-Arabism, and the role of the security factor in the formation of foreign policy. It is also substantiated that the influence of internal competition and external forces in the region determines the complex and contradictory nature of the foreign policy of the Arab states.